1989
DOI: 10.1016/0021-9991(89)90155-1
|View full text |Cite
|
Sign up to set email alerts
|

A boundary integral approach to unstable solidification

Abstract: We consider the supercooled Stefan problem with a general anisotropic curvature-and velocity-dependent boundary c<;mdition on the moving interface. This is a well-known model for pattern formation in unstable solidification.We reformulate the problem in terms of a quasilinear history-dependent singular integral equation for the velocity of the boundary. Using this equation, we carry out a new linear stability analysis of a planar solidification front with a general boundary condition. This analysis disagrees w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…We have considered other ways to enforce this condition, but we have found that just explicitly forcing these coefficients to be 1 and 0, respectively, performs the best numerically. We remark that Strain also noted this difficulty in [48], but he did not seem to employ a correction of it computationally.…”
Section: X(~t)=x(ot)+~i 1 L ~2~ Doclmentioning
confidence: 97%
See 1 more Smart Citation
“…We have considered other ways to enforce this condition, but we have found that just explicitly forcing these coefficients to be 1 and 0, respectively, performs the best numerically. We remark that Strain also noted this difficulty in [48], but he did not seem to employ a correction of it computationally.…”
Section: X(~t)=x(ot)+~i 1 L ~2~ Doclmentioning
confidence: 97%
“…See, for example, Strain [48] in the context of unstable solidification, or Goldstein and Petrich [ 20 ] in the context of integrable curve dynamics. We derive it here for purposes of completeness and illustration.…”
Section: (1) N=(-ys Xs)=(-yx)/s~mentioning
confidence: 99%
“…In these two new variables, the surface tension term has a very simple form: Sκ α = S(θ α /σ) α . This approach has been used previously by Kessler, Koplik and Levine [25] for interface evolution problems, by Strain [40] in the context of solidification, by Goldstein and Petrich [21] for integrable closed curve dynamics, and by Meiburg and Homsy [32] for Hele-Shaw flows.…”
Section: A Boundary Integral Reformulation For Two Fluid Interfacesmentioning
confidence: 99%
“…Boundary integral methods are a popular choice for simulations of interfacial flows and have been used extensively to compute nonlinear surface wave [6], [19], [30], [35], [37], vortex sheet (no density difference) motion [3], [23], [26], [27], [36], [38], Rayleigh-Taylor instability [5], [35], [44], interfaces in Hele-Shaw cells [17], [24], and crystal growth and solidification [29], [40]. The advantage of boundary integral methods is that they reduce the dimension of the problem by involving quantities along the interface only [34].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical results agreed closely with linear stability theory and predicted correct tip-splitting phenomena in the nonlinear regime. The method and numerical results are presented in (Strain, 1989).…”
Section: Moving Interfacesmentioning
confidence: 99%